Experimental and numerical investigation of dynamic plastic behavior of tube with different thickness distribution under axial impact. (December 2016) - Rajabiehfard, R.; Darvizeh, A.; Alitavoli, M.; Sadeghi, H.; Noorzadeh, N.; Maghdouri, E.
Abstract: In this study, the dynamic behavior of uniform thickness, stepped thickness and functionally graded thickness tubes under axial impact are investigated experimentally and numerically. A striking mass has been used to impact tubes. Experimental tests are performed by using gas gun and numerical results are obtained by FE simulation. The effect of thickness distribution on shortening, energy absorption, axial force and buckling shape of tubes are investigated. It is found that a change in thickness distribution of tube can convert the buckling shape from buckling with mild folds to progressive buckling and vice versa. In addition, it is found that stepped thickness tube can be an approximate of functionally graded thickness tube which in this case almost, their behavior is identical. This study reveals that stepped thickness and functionally graded thickness tubes in comparison with uniform thickness tube absorb the same energy with more shortening and less peak load or less mean load; thus, they are better energy absorption specimens. With comparing experimental and numerical results, it is found that there is a good agreement between them. Highlights: The effect of different thickness distribution of steel tubes subjected to axial high velocity impact is investigated. Experimental tests are performed by using gas gun and numerical results are obtained by FE simulation. The effect of thickness distribution on shortening, energy absorption, axial force and buckling shape of tubes is investigated.